The impact of the ROPO effect in the clothing industry - Mróz-Gorgoń, Barbara; Szymański, Grzegorz (Economics and Business Review, 2018)
The number of Internet users in Poland is permanently increasing, the vast majority of Y generation use the Internet at least once a week, while the youngest generation (born after 2000) consider the Internet to be a part of their normal life. Shopping online should be something natural and ordinary for Internet users and the main barriers of the development of e-commerce such as security of transactions, time and costof delivery are regarded as a standard and truism. The ROPO effect is a major problem for the rapid development of the e-commerce sector. However, the analyzed clothing industry, due to the individual characteristics of products, is a different e-commerce area than others. The obtained results indicate that about 33% of women and men use the Internet as a place to get information about clothing products. Research Online, Purchase Offline, that is, search for information, reviews, or online prices, while buying in the traditional way. The purpose of the publication is to identify the size of the ROPO effect the clothing industry. In order to meet this goal, we analyzed the results of more than 4.000 respondents who have recently purchased clothing products.